The Effectiveness of Cooperative Learning of Assisted Media Integrated Reading and Composition Cergam on Skills Reading Understanding - Fitri Suciyati; Septiyati Purwandari; Arif Wiyat Purnanto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effectiveness of the cooperative integrated reading and composition learning model assisted by CERGAM media on the reading comprehension skills of grade II students in Gunungpring Village, Muntilan District. This research is an experimental research with a design (One Group Pretest-Posttest). The samples taken for this study were 15 second grade students in Gunungpring Village, Muntilan. The sampling technique used is a saturated sample. The method of data collection was done by using a test in the form of a multiple choice test. Test the validity to measure the questions pretest and posttest using Product Moment, reliability using Cronbach's Alpha. The data analysis technique in this study used the normality test using the Shapiro-Wilk and the hypothesis using the Wilcoxon test with the help of the IBM SPSS version 25.00 program for windows. The results showed that cooperative integrated reading and composition learning assisted by CERGAM media had a positive effect on the second grade students' reading comprehension skills. This is evidenced by the results of the hypothesis test of data analysis on pretest and posttest questions related to fable material using the Wilcoxon Test with results showing that the Z value obtained is -3.413b with Asymp Sig. 2 tails of 0.001. The results of this study can be concluded that the use of a cooperative integrated reading and composition model assisted by comic media has a positive effect on reading comprehension skills.